Pengaruh Metode Discovery Learning dan Drill serta Motivasi Belajar terhadap Hasil Belajar Bolavoli siswa Kelas VIII SMPN 1 Kediri - Ulum, Miftachul (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2018)
Starting from the dissatisfaction of the relatively low bolavoli value, then developed the method of learning Discovery Learning and drill and motivation to learn. The purpose of this research is to know: is there any influence between discovery learning method with drill method to learning result of bolavoli; is there any influence of learning motivation on learning outcomes of bolavoli; and is there any interaction between Discovery Learning method and Drill method with learning motivation toward learning outcome of bolavoli at grade VIII student of SMPN 1 Kediri. The method of this research is experimental method. Sample 134 students (4 classes) from a population of 342 students (10 classes). This data collection technique with a questionnaire of learning motivation and test results of learning bolavoli. Data analysis technique used is ANAVA. The results of data analysis for the first hypothesis found price F of 0.379 with a significance value of 0.539 and for the second hypothesis found price F of 5.712 with a significance value of 0.018 and for the third hypothesis found price F of 4.232 with a significance value of 0.042l. Based on the results of research and the results of data analysis, can be obtained conclusion: There is no influence between the method of Discovery learning with Drill method of learning outcomes Volleyball; There is an influence of learning motivation on learning outcomes of Bolavoli; There is an interaction between Discovery Learning method and Drill method with learning motivation to Volleyball learning result.